Perinatal depression in refugee and labour migrant women on the Thai-Myanmar border: prevalence, risk factors and experiences - Fellmeth, G (2018)
Background: Perinatal depression is a significant contributor to maternal morbidity and mortality worldwide. Left untreated, perinatal depression has severe and far-reaching consequences for women, their families and wider society. Migrant women, including labour migrants and refugees, may be particularly prone to developing perinatal depression as a result of multiple stressors associated with displacement. Despite the vast majority of global migration flows occurring within low- and middle-income countries, evidence from these regions is severely lacking. This research addresses this imbalance by examining perinatal depression in migrant women living on the Thai-Myanmar border: a resource-poor setting of political tension and socio-economic disadvantage. Aims: This research aims to review the existing evidence around perinatal depression among migrant women from low- and middle-income settings; identify an appropriate tool to detect perinatal depression in migrant women on the Thai-Myanmar border; determine the prevalence of, and risk factors for, perinatal depression in this setting; explore women's experiences of perinatal depression; and develop recommendations for policy and practice. Methods: A sequential-exploratory mixed-methods design was used. The research included the following five study components: a systematic literature review; a validation study to identify a culturally-acceptable and appropriate assessment tool; a prospective cohort study of migrant women on the Thai-Myanmar border followed-up from the first trimester of pregnancy to one month post-partum; in-depth interviews with a subgroup of women with severe perinatal depression; and an informal exploration of stakeholder views. Findings: The systematic review found a wide range in prevalence of perinatal depression among migrant women and confirmed the absence of studies conducted in low-and middle-income destination countries. A total of 568 migrant women on the Thai-Myanmar border participated in the prospective cohort study, of whom 18.5% experienced moderate-severe depression and 39.8% experienced depression of any severity during the perinatal period. Almost a third (29%) of women reported suicidal ideation. Interpersonal violence (OR 4.5), experience of trauma (OR 2.4), a self-reported history of depression (OR 2.3) and perceived insufficiency of social support (OR 2.1) were significantly associated with perinatal depression. Lives of women with severe perinatal depression were characterised by difficult partner relationships, alcohol use among partners and interpersonal violence. A lack of mental health services currently limits the effective management of perinatal depression in this setting. Alongside training of health staff, primary, secondary and tertiary prevention efforts are required to effectively address perinatal depression on the Thai-Myanmar border.